Static buckling analysis and geometrical optimization of magneto-electro-elastic sandwich plate with auxetic honeycomb core - Quang, Vu Dinh; Quan, Tran Quoc; Tran, Phuong (Thin-walled structures, 2022)
The nonlinear static buckling analysis of magneto-electro-elastic sandwich plate on Pasternak-type elastic foundations subjected to the mechanical, thermal, electric and magnetic loadings is presented in this paper. The sandwich plate is composed of an auxetic honeycomb core with negative Poisson’s ratio and two face sheets made of magneto-electro-elastic​ material. The system basic equations are derived based on the Reddy’s higher order shear deformation plate theory taking into account the effect of von Kármán the kinematic nonlinearity and initial imperfection. The form of possible solutions and electric, magnetic potentials are chosen as trigonometric functions based on two cases of boundary conditions. The relationship between axial compressive loading and dimensionless deflection amplitude is determined by using the Galerkin method. For optimization problem, the Bees algorithm is applied to obtain the maximum value of critical buckling load of the sandwich plate which depends on five geometrical and material parameters. The effects of elastic foundations, temperature increment, geometrical parameters and electric and magnetic potentials on the stability characteristics are investigated in numerical results. The accuracy and reliability of present approach is confirmed by comparisons with the existing results in the literature. [Display omitted] •The nonlinear static buckling analysis of sandwich plate is presented.•The sandwich plate consists of an auxetic honeycomb core and two face sheets made of magneto-electro-elastic material.•The sandwich plate is subjected to the combination of mechanical, thermal, electric and magnetic loadings.•The axial compressive loading–dimensionless deflection amplitude relationship is determined by using the Galerkin method.•Bees Algorithm is applied to obtain the maximum value of critical buckling load.